Effect of delayed CNI-based immunosuppression with Advagraf on liver function after MELD-based liver transplantation (IMUTECT) - Richter, Susanne; Polychronidis, Georgios; Gotthardt, Daniel; Houben, Philipp; Giese, Thomas; Sander, Anja; Dörr-Harim, Colette; Diener, Markus K.; Schemmer, Peter (BMC surgery, 2014)
MELD-based allocation for liver transplantation follows the “sickest-patient-first” strategy. The latter patients present with both, decreased immune competence and poor kidney function which is further impaired by immunosuppressants.